2023
DOI: 10.1186/s12920-023-01519-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of immune-related biomarkers and potential regulators and therapeutic targets for diabetic kidney disease

Abstract: Background Diabetic kidney disease (DKD) is a major complication of diabetes and the leading cause of end-stage renal disease worldwide. Renal inflammation and infiltration of immune cells contribute to the development and progression of DKD. Thus, the aim of the present study was to identify and validate immune-related biomarkers and analyze potential regulators including transcription factors (TFs), microRNAs (miRNAs), and drugs for DKD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…During AKI, the expression of the Kl gene in renal tubular cells is reduced, and its restoration can alleviate kidney damage and promote AKI recovery [26,27]. A significant decrease in GHR expression was observed in diabetic kidney disease, and GHR antagonists protected against diabetic kidney disease [28,29]. Interestingly, we observed an acute downregulation of Kl and Ghr in PTS1 and PTS2 cells, which was negatively correlated with Ezh2 expression.…”
Section: Discussionmentioning
confidence: 63%
“…During AKI, the expression of the Kl gene in renal tubular cells is reduced, and its restoration can alleviate kidney damage and promote AKI recovery [26,27]. A significant decrease in GHR expression was observed in diabetic kidney disease, and GHR antagonists protected against diabetic kidney disease [28,29]. Interestingly, we observed an acute downregulation of Kl and Ghr in PTS1 and PTS2 cells, which was negatively correlated with Ezh2 expression.…”
Section: Discussionmentioning
confidence: 63%
“…It is worth noting some differences found in this study compared to previous studies. 23 Differences in GLB, lymphocyte, and PLT levels between the 2 groups were not significant ( P > .05) indicating that immune factors may not be the main cause of DKD progression. Moreover, no significant difference was observed in blood ALT or LDL-C levels between the 2 groups.…”
Section: Discussionmentioning
confidence: 87%
“…With the rapid development of the economy and society, the prevalence of DKD is gradually increasing worldwide which imposes a heavy economic and social burden. Our previous bioinformatics analysis found that RES can reverse gene expression abnormalities in DKD patients’ glomerulus [ 37 ]. Moreover, as a natural active ingredient, RES has the characteristics of being non-toxic and harmless [ 38 ].…”
Section: Discussionmentioning
confidence: 99%